Virtual Choir Indonesia Menyanyi (VCIM): Uniting Indonesia through Music and Technology - Steven, Ken; Widodo, Widodo; Utomo, Udi; Batubara, Junita (Journal of Posthumanism, 2025)
This study discussed the Virtual Choir Indonesia Menyanyi (VCIM) where VCIM utilizes digital technology to build harmony in the diversity of Indonesian culture. Through this study, various ethnic elements were connected to an inclusive platform through collaborative musical expression. This initiative not only enriches the nation’s cultural heritage but also strengthens unity amidst differences, showing that music can unite the hearts and souls of the Indonesian people. In the era of globalization and technological advancement, virtual choirs have become an effective platform for cross-cultural collaboration, enabling the creation of collective musical works that transcend geographical boundaries. This study aims to analyze how digital technology in Virtual Choir Indonesia Menyanyi facilitates the unification of voices from various cultural backgrounds while also becoming a medium to introduce Indonesian national identity to a global audience. Using a qualitative approach based on descriptive-analytical analysis, this study explores the production process, dynamics of virtual collaboration, and social and cultural impacts of this project. Data were collected through in-depth interviews with participants, content analysis of virtual choir recordings, and surveys of international audiences regarding perceptions of Indonesian culture. The results of the study show that VCIM has not only succeeded in creating a harmonious musical performance but has also made a significant contribution to increasing global recognition of Indonesia’s cultural diversity. This study also confirms that digital platforms not only function as communication tools, but also play a transformative role in strengthening intercultural connections, fostering unity in diversity, and strengthening national identity at the international stage.